The NOW regional coupled model: Application to the tropical Indian Ocean climate and tropical cyclone activity. (5th August 2014) - Samson, G.; Masson, S.; Lengaigne, M.; Keerthi, M. G.; Vialard, J.; Pous, S.; Madec, G.; Jourdain, N. C.; Jullien, S.; Menkes, C.; Marchesiello, P.
Abstract This paper presents the NOW regional coupled ocean‐atmosphere model built from the NEMO ocean and WRF atmospheric numerical models. This model is applied to the tropical Indian Ocean, with the oceanic and atmospheric components sharing a common ¼° horizontal grid. Long experiments are performed over the 1990–2009 period using the Betts‐Miller‐Janjic (BMJ) and Kain‐Fritsch (KF) cumulus parameterizations. Both simulations produce a realistic distribution of seasonal rainfall and a realistic northward seasonal migration of monsoon rainfall over the Indian subcontinent. At subseasonal time scales, the model reasonably reproduces summer monsoon active and break phases, although with underestimated rainfall and surface wind signals. Its relatively high resolution results in realistic spatial and seasonal distributions of tropical cyclones, but it fails to reproduce the strongest observed cyclone categories. At interannual time scales, the model reproduces the observed variability associated with the Indian Ocean Dipole (IOD) and the delayed basin‐wide warming/cooling induced by the El Niño Southern Oscillation (ENSO). The timing of IOD occurrence in the model generally matches that of the observed events, confirming the influence of ENSO on the IOD development (through the effect of lateral boundary conditions in our simulations). Although the KF and BMJ simulations share a lot in common, KF strongly overestimates rainfall at all time scales. KF also overestimates the number of simulated cyclones by a factor two, while simulating stronger events (up to 55 m s−1) compared to BMJ (up to 40 m s−1). These results could be related to an overly active cumulus parameterization in KF.